2021
DOI: 10.1158/0008-5472.can-20-3790
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DDX3X Triggers Antitumor Immunity via a dsRNA-Mediated Tumor-Intrinsic Type I Interferon Response

Abstract: Induction of nucleic acid sensing–mediated type I interferon (IFN) has emerged as a novel approach to activate the immune system against cancer. Here we show that the depletion of DEAD-box RNA helicase 3X (DDX3X) triggers a tumor-intrinsic type I IFN response in breast cancer cells. Depletion or inhibition of DDX3X activity led to aberrant cytoplasmic accumulation of cellular endogenous double-stranded RNAs (dsRNA), which triggered type I IFN production through the melanoma differentiation-associated gene 5 (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…[ 40 ] Accumulating reports have showed that intracellular dsRNA could activate innate immune response and stimulate production of type I IFN to prevent tumorigenesis. [ 41 , 42 ] A recent work reveals that circNDUFB2 activates anti‐tumor immunity to suppress lung cancer growth. [ 31 ] How circRNA regulates innate immunity in CRC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Accumulating reports have showed that intracellular dsRNA could activate innate immune response and stimulate production of type I IFN to prevent tumorigenesis. [ 41 , 42 ] A recent work reveals that circNDUFB2 activates anti‐tumor immunity to suppress lung cancer growth. [ 31 ] How circRNA regulates innate immunity in CRC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that DDX3X prevents antiviral response against endogenous dsRNAs in the steady-state cell condition (without a viral infection or synthetic dsRNA treatment) ( Choi et al, 2021 ). A small fraction of endogenous dsRNAs was detected in the cytoplasm.…”
Section: Introductionmentioning
confidence: 81%
“…We found that 1) loss of DDX3X or inhibiting DDX3X resulted in the aberrant accumulation of endogenous dsRNAs in the cytoplasm of breast cancer cells; 2) the accumulation of dsRNAs activated the dsRNA-sensing pathway via mainly MDA5 and activation of nuclear factor kappa B (NF-κB) pathway followed by IFN- β production and enhanced antigen presentation in the DDX3X-depleted cells; 3) DDX3X-depleted cancer cells demonstrated the inhibited cancer proliferation and suppressed tumor growth in in vivo mouse studies. DDX3X-depleted breast tumor also exhibited tumor-intrinsic innate immune activation and increased tumor-infiltrated cytotoxic T cells and DCs in a syngeneic mouse model ( Figure 1 ) ( Choi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, type I interferon signaling pathway is one result of GO enrichment analysis, its function has an important relationship with the function of pDCs. Choi et al (50) reported that activation of type I interferon is a novel approach to activate the immune system against cancer. NOD-like receptor (NLRs) signaling pathway is another important signaling pathway that is worthy of attention.…”
Section: Discussionmentioning
confidence: 99%